The extent of antipsychotic use in Australian residential aged care facilities and interventions shown to be effective in reducing antipsychotic use: A literature review. (May 2020) - Westaway, Kerrie; Sluggett, Janet; Alderman, Christopher; Moffat, Anna; Procter, Nicholas; Roughead, Elizabeth
At least half of all residents of Australian residential aged care facilities have dementia. Most residents living with dementia will at some stage experience behavioural and psychological symptoms of dementia (BPSD), which can be challenging to manage and distressing for the resident, their family and carers. This literature review examined the prevalence of antipsychotic use in Australian residential aged care facilities, which may be used to manage BPSD only after non-pharmacological treatments have failed. Sixteen studies assessing care between 2000 and 2017 were identified and reviewed. The proportion of residents prescribed an antipsychotic ranged from 13% to 42%. Evidence from six Australian interventions showed that the antipsychotic use can be reduced, especially when non-pharmacological interventions that are individualised to the person and the behaviour are implemented. Research has shown that antipsychotics can be tapered and ceased without re-emergence of behavioural symptoms in many instances. Multidisciplinary, multi-strategic approaches have demonstrated effectiveness in reducing antipsychotic use by up to 3% (absolute reduction) in the aged-care setting.